A passive optical bidirectional network design with Spectral partitioning of a wide band font (2018)
This paper presents the design of a passive optical network that approach the totally wide band of a light font in order to generate differents carrier signals that can be approach for a considerable cuantity of ussers much better and more like than the actually passive optical networks and realize a variety of network when the principle is a unique light font with download and upload carriers throught the same network instead a unique light font to unique user. Inside the design, the spectral partitionign is approach in the way that divides the light Font with a sepparation of 0,11nm between the carriers, consider the wide band LED has 100nm of bandwith, in order to obtain a high number of carriers in the third window. Approaching this fenomenum, the costs in the implementations could be reduced in the PON systems.